Analysis of Factors Affecting Human Development Index in Special Regional of Yogyakarta - Nurul Fadillah; Lilies Setiartiti (Universitas Muhammadiyah Yogyakarta, 2021)
This study aims to analyze the factors affecting the Human Development Index in the Special Regional of Yogyakarta. This study uses secondary data from the Central Bureau of Statistics (BPS) and the Regional Asset Financial Management Agency (BPKAD) in the Special Regional of Yogyakarta, namely Yogyakarta City, Sleman Regency, Bantul Regency, Kulon Progo Regency, and Gunung Kidul Regency in 2013- 2018. Meanwhile, the analysis tools used in the study used the Panel Data Method with the Fixed Effect Model approach. This study indicates that the Gross Regional Domestic Product (PDRB) and government spending in the health sector positively and significantly affect the Human Development Index. Government spending in the education sector has a negative and insignificant effect on the Human Development Index (HDI).